Idiopathic Normal Pressure Hydrocephalus and Elderly Acquired Hydrocephalus: Evaluation With Cerebrospinal Fluid Flow and Ventricular Volume Parameters - He, Wen-Jie; Zhou, Xi; Long, Jia; Xu, Qi-Zhong; Huang, Xian-jian; Jiang, Jun; Xia, Jun; Yang, Guang (Frontiers in Aging Neuroscience, 2020)
Purpose: To investigate differences in cerebrospinal fluid (CSF) flow through the aqueduct and to determine whether there is a relationship between CSF flow and ventricular volume parameters in idiopathic normal pressure hydrocephalus (iNPH) patients, elderly acquired hydrocephalus patients and age-matched healthy volunteers by phase-contrast MR (PC-MR). Methods: A total of 40 iNPH patients and 41 elderly acquired hydrocephalus patients and 26 age-matched healthy volunteers in the normal control (NC) group were included between November 2017 and October 2019 in this retrospective study. The following CSF flow parameters were measured with PC-MR: peak velocity, average velocity (AV), aqueductal stroke volume (ASV), net ASV and net flow. The following ventricular volume parameters were measured: ventricular volume (VV), brain volume, total intracranial volume and relative VV. Differences between the iNPH and acquired hydrocephalus groups were compared Mann-Whitney U test and correlations between CSF flow and ventricular volume parameters were assessed using the Spearman correlation coefficient. Results: ASV was significantly higher in the iNPH and acquired hydrocephalus groups than in the NC group, but did not differ significantly between the iNPH group and acquired hydrocephalus group. The AV, net ASV and net flow in the iNPH and acquired hydrocephalus groups were significantly higher than those in the NC group (P<0.0001), and those in the acquired hydrocephalus group were significantly higher than those in the iNPH group (P=0.01, P=0.007, P=0.002, respectively). The direction of the AV and net ASV significantly differed among the three groups. There were no associations between the volume parameters and CSF flow according to PC-MR among the three groups. Conclusions: Compared with iNPH, elderly acquired hydrocephalus demonstrated higher CSF hyperdynamic flow. Although increased CSF flow may contribute to further changes in ventricular morphology, there is no linear relationship between them. These findings might help increase our understanding of flow dynamics in iNPH and elderly acquired hydrocephalus.